CONSUMER PROTECTION IN RELATION WITH THE EUROPEAN BUSINESS ENVIRONMENT - Gheorghiu, Gabriela; Nancu, Dorinela; Alexandra, Dănilă (European Scientific Journal, ESJ, 2015)
The present paper highlights the importance of protecting consumers in their relations with the representatives of business environment in general and with those of European business environment in particular, in order to enhance the benefits they can get from transactions carried out in the market and to ensure that they can take full advantage of the European single market. Analyzing the results of research undertaken by the European Commission, which regularly monitors markets and national consumer conditions and assesses business attitudes toward cross-border trade and consumer protection, the paper argue that consumer environments differ considerably across European Union‘s Member States. Furthermore, it identifies the persistence of unfair commercial practices and low knowledge of consumer rights among both consumers and businesses as issues of particular concern.